Peran program muhadloroh terhadap pengembangan maharah kalam santri ma’had man 2 lamongan - Candra, Zaqias (Maliki Interdisciplinary Journal, 2024)
This article discusses the importance of the muhadloroh program at MAN 2 Lamongan in developing maharah kalam, or Arabic speaking skills, among students. Maharah kalam is one of the four essential language skills that Arabic learners must master, and the muhadloroh program is considered effective for training public speaking abilities. Activities within this program include speech text preparation, group discussions, muhadloroh rehearsals, and presentations in front of an audience. Despite the program's significant potential, several supporting and hindering factors affect its success. Positive factors include teacher support, adequate facilities, and student commitment, while challenges such as variations in Arabic proficiency, lack of self-confidence, and limited practice outside the classroom exist. Through ongoing evaluation and the adaptation of more varied teaching methods, the muhadloroh program can be more effective in enhancing students' speaking skills while strengthening their understanding of the Arabic language and culture. This research provides in-depth insights into the role of the muhadloroh program in Arabic language education, as well as the factors influencing its success.